The Potential of Seaweed Salt as an Alternative Low Natrium Salt: Safety and Sensory Test - Lindarsih Notowidjojo; Purwantyastuti Ascobat; Saptawati Bardosono; Jana Tjahjana (World Nutrition Journal, 2021)
Indonesia is one of the largest producers of red seaweed in the world, but there is very little research done on the role of red seaweed in the health sector. This study is about red seaweed type Euchema cottoni and it’s potential as seaweed salt that has lower natrium and rich in other minerals.This research was divided into two phases and conducted from December 2016 to March 2017. The first phase is a safety analysis in terms of metal, mold and bacteria contamination of seaweed from three different places of Indonesia: Saumlaki, Maluku; Nusa Dua, Bali and Flores, Nusa Tenggara Barat. After the seaweed safety was selected, the seaweed was made into powder at Industrial Research and Development Agency (BPPT), Tangerang. The seaweed powder mixed with ordinary salt with four type of concentrations were subjected to a salty sensory test by nine panellists who have been working at the food production at Hospital for at least one year. The second phase was to do acceptance sensory test of the seaweed salt product taste against a concentration that was selected in first phase to first-degree hypertensive subjects aged 25–59 years by using soup as the meal-media. Chi-square test was used to analyse the difference.Seaweed from Saumlaki, Maluku was selected as the safest seaweed due to it’s lowest content of metal, mold and bacterial contaminations. The ratio of seaweed powder to ordinary salt powder 1:1 was selected by nine panellists in salty sensory test. Analysis of minerals from the seaweed salt product found that besides the lower sodium and Iodium content, it’s potassium and magnesium content were much higher than ordinary salt. Salty taste test by 62 respondents with first degree hypertension with age 25-59 years showed no significant difference in saltiness between seaweed salt and ordinary salt.In conclusion, the seaweed salt product with a 1:1 ratio to ordinary salt powder is safe and acceptable to be used as an alternative low Na salt.